Britain in the wider world, Roman times-present - Riley, Michael; Ford, Alex; Goudie, Kath (Understanding history, 2019)
Help every pupil to know more, look closer, think deeper and write better as they develop their historical knowledge and skills throughout Key Stage 3 and get 'GCSE-ready'. Exploring the stories of fascinating people, places and events through an enquiry approach, this Student Book familiarises KS3 pupils with the different ways of thinking required for thematic, period, depth and site studies at GCSE. - Easily and cost-effectively implement a new KS3 curriculum: this coherent single-book course contains 120 lessons that experienced and non-specialist teachers can deliver with confidence, across a two or three-year KS3 - Establish strong foundational knowledge of British History: the content has been meticulously selected to provide a chronological spine that contextualises GCSE content, saving you valuable time when teaching GCSE - Focus on building writing skills: GCSE-style command words and question types are introduced gradually, developing the extended writing skills that pupils need to reach the highest marks, whichever GCSE specification you follow - Effectively assess and demonstrate progress: regular activities throughout the Student Book lead to end-of-enquiry tasks, supporting both formative and summative assessment of pupils' conceptual understanding and writing skills - Generate enthusiasm and respect for historical evidence: pupils are encouraged to use sources and interpretations as part of their historical investigations, leading to a natural improvement in their analytical and evaluative skills.